Effect of pH on Inorganic Carbon Uptake in Algal Cultures - Azov, Y. (1982)
Biomass production by the green algae Scenedesmus obliquus and Chlorella vulgaris in intensive laboratory continuous cultures was considerably affected by the pH at which the cultures were maintained. Carbon photoassimilation experiments revealed that pH values in the range of 8 to 9 were important for determining the free CO(2) concentrations in the medium. With higher pH values, additional pH effects were observed involving a decrease in the relative high affinity of low CO(2)-adapted algae to free CO(2). The carbon uptake rate by high CO(2)-adapted algae after transfer to low free CO(2) medium was characterized by a lag period of about 30 min, after which the affinity of the algae to CO(2) increased considerably. Both continuous growth and carbon uptake experiments indicated that artificially maintained high free CO(2) concentrations are recommended for maximal production in intensive outdoor algal cultures.